Understanding Preservice Teachers’ Attitudes Toward AI in Education: Implications for Future Professional Development - Tiyas Abror Huda; Sodikin Sodikin (AI and Developmental Insights in Education, 2025)
This study examined the educational problem of how preservice teachers perceive Artificial Intelligence (AI) in education and the extent to which their attitudes predict readiness to use AI in future teaching practice. Using a quantitative, cross-sectional survey design, data were collected from 212 preservice teachers enrolled in teacher-education programs. Participants completed the 22-item Attitudes Toward AI in Education Scale, which measured perceived usefulness, ethical and privacy concerns, pedagogical confidence, and professional identity readiness. Descriptive statistics indicated generally positive attitudes, while regression analyses showed that perceived usefulness and pedagogical confidence significantly predicted AI readiness, ethical concerns had a small negative effect, and professional identity readiness was not significant. These results highlight the central role of confidence and perceived value in shaping readiness, while also underscoring the need to address ethical apprehensions in teacher preparation. The study contributes a validated measurement framework and offers evidence-based guidance for designing AI-focused professional development in teacher education.